2011
DOI: 10.1021/jz2005573
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Coherent Anti-Stokes Raman Scattering with Time-Dependent Density Functional Theory: Vacuum and Surface Enhancement.

Abstract: We present the first density functional simulations of coherent anti-Stokes Raman scattering (CARS) and an analysis of the chemical effects upon binding to a metal surface. Spectra are obtained from first-principles electronic structure calculations and are compared with available experiments and previously available theoretical results following from Hartree–Fock polarizability derivatives. A first approximation to the nonresonant portion of the CARS signal is also explored. We examine the silver pyridine clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 71 publications
(144 reference statements)
1
19
0
Order By: Relevance
“…While the dispersive nature of the lineshapes was originally hypothesized to be purely Fano-like interferences, 15 our analysis suggests that they are a combination of two Fano-like contributions. Similar to previously observed dispersive lineshapes that originate from multiple physical interference processes, 21,22 the lineshapes in this work are attributed to interference of the real and imaginary components of the Raman susceptibility with the LFE of the Stokes field interacting with a plasmonic particle.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…While the dispersive nature of the lineshapes was originally hypothesized to be purely Fano-like interferences, 15 our analysis suggests that they are a combination of two Fano-like contributions. Similar to previously observed dispersive lineshapes that originate from multiple physical interference processes, 21,22 the lineshapes in this work are attributed to interference of the real and imaginary components of the Raman susceptibility with the LFE of the Stokes field interacting with a plasmonic particle.…”
Section: Discussionsupporting
confidence: 89%
“…20 Research into the lineshapes observed in surfaceenhanced coherent Raman scattering has focused primarily on SECARS. 21,22 In SECARS, dispersive lineshapes in the vibrational spectrum are observed due to interference of the vibrationally resonant signal with electronically resonant four-wave mixing signals, similar to the lineshapes seen in CARS. One paper has investigated the plasmonicenhancement in SE-SRS; however, the theory only considered single vibrational modes and resulted in Lorentzian lineshapes.…”
Section: Plasmonically Enhanced Coherent Raman Scatteringmentioning
confidence: 76%
See 1 more Smart Citation
“…Time-resolved tip-enhanced CARS spectroscopy7 and subwavelength microscopy could be realized by extension of the present approach. Spectral interpretation could be facilitated by using higher levels of theory and by direct modeling of the surface-enhanced CARS signals28. With further developments tr-SECARS could achieve ultrashort sub-picosecond signal acquisition and single shot real-time detection capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic CARS susceptibilities have been simulated for this work using time‐dependent density functional theory, employing the PBE0 functional and def2‐TZVP basis within a locally modified version of the TURBOMOLE program package. At the level of theory employed, the CARS susceptibility is modeled as a product of polarizability derivatives along harmonic nuclear modes.…”
Section: Computational Modelingmentioning
confidence: 99%